2016
DOI: 10.1128/jvi.02172-15
|View full text |Cite
|
Sign up to set email alerts
|

Macaque Monoclonal Antibodies Targeting Novel Conserved Epitopes within Filovirus Glycoprotein

Abstract: Filoviruses cause highly lethal viral hemorrhagic fever in humans and nonhuman primates. Current immunotherapeutic options for filoviruses are mostly specific to Ebola virus (EBOV), although other members of Filoviridae such as Sudan virus (SUDV), Bundibugyo virus (BDBV), and Marburg virus (MARV) have also caused sizeable human outbreaks. Here we report a set of pan-ebolavirus and pan-filovirus monoclonal antibodies (MAbs) derived from cynomolgus macaques immunized repeatedly with a mixture of engineered glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 48 publications
5
96
0
1
Order By: Relevance
“…In a mouse model of EBOV infection, FVM04 was fully protective when used in two doses (2 h and 3 days postchallenge). When given a single dose 3 days postchallenge, survival rate was 40% [53].…”
Section: Development Of Cross-reactive Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of EBOV infection, FVM04 was fully protective when used in two doses (2 h and 3 days postchallenge). When given a single dose 3 days postchallenge, survival rate was 40% [53].…”
Section: Development Of Cross-reactive Antibodiesmentioning
confidence: 99%
“…Therefore, broadly protective treatment options are needed. Multiple mAbs have been generated, that elicit cross-reactivity in vitro and efficacy in mouse models for different Ebola virus species [49,50] including Marburg virus [51][52][53]. Furuyama et al generated mAb 6D6, which was found to efficiently neutralize the infectivity of vesicular stomatitis virus (VSV) pseudo-typed with GPs of all known Ebola viruses (EBOV, SUDV, TAFV, BDBV, and RESTV), but not Marburg virus (MARV).…”
Section: Development Of Cross-reactive Antibodiesmentioning
confidence: 99%
“…However, limited but promising therapeutic evidence is available in humans [5,32]. Up to now, over 500 mAbs against EBOV have been extracted from recovered patients [15,17,33,34] or developed from animal models [35,36]; however, most of those mAbs have not been checked in clinical trials. To date, about 20 kinds of EBOV mAbs have been identified and characterized, several of them were found promising in non-human primate models, such as mAb114, MIL77E, MB-003, ZMab, and ZMapp TM [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…A handful of BDBV-specific monoclonal or polyclonal murine, rabbit or crab-eating macaque antibodies (Ou et al 2011;Holtsberg et al 2015;Keck et al 2015;Wang et al 2015), BDBV …”
Section: Bundibugyo Virusmentioning
confidence: 99%
“…Several serological or nucleic-acid based RESTVspecific diagnostic systems have been described (Kalter et al 1995;Ksiazek et al 1999;Niikura et al 2001;Ikegami et al 2002bIkegami et al , 2003aOu et al 2011). RESTV-specific monoclonal or polyclonal murine, rabbit or crab-eating macaque antibodies (Ou et al 2011;Holtsberg et al 2015;Keck et al 2015;Wang et al 2015), RESTV cross-reactive murine antibodies (Fusco et al 2015;Wang et al 2015;Furuyama et al 2016), RESTV cross-reactive murine scFvs and IgNAR Vs raised against inactivated EBOV particles (Goodchild et al 2011) are available.…”
Section: Reston Virusmentioning
confidence: 99%